2011
DOI: 10.1371/journal.ppat.1002357
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism for Bacterial Susceptibility to Zinc

Abstract: Transition row metal ions are both essential and toxic to microorganisms. Zinc in excess has significant toxicity to bacteria, and host release of Zn(II) at mucosal surfaces is an important innate defence mechanism. However, the molecular mechanisms by which Zn(II) affords protection have not been defined. We show that in Streptococcus pneumoniae extracellular Zn(II) inhibits the acquisition of the essential metal Mn(II) by competing for binding to the solute binding protein PsaA. We show that, although Mn(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
496
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 425 publications
(527 citation statements)
references
References 50 publications
29
496
1
1
Order By: Relevance
“…Recombinant PsaA was cloned from S. pneumoniae D39 genomic DNA, gene SPD_1463, into pCAMcLIC01-PsaA as previously described [19]. The recombinant sequence of PsaA 8 …”
Section: Expression and Purification Of Psaa And Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant PsaA was cloned from S. pneumoniae D39 genomic DNA, gene SPD_1463, into pCAMcLIC01-PsaA as previously described [19]. The recombinant sequence of PsaA 8 …”
Section: Expression and Purification Of Psaa And Variantsmentioning
confidence: 99%
“…It has a two-lobed organization comprising of N-and C-terminal (β/α) 4 -domains linked by a rigid helix, and bisected by a cleft in which the Mn 2+ ion binds [18,19] (Figure 1a). …”
Section: Introductionmentioning
confidence: 99%
“…Such a connection between zinc resistance and higher tolerance to oxidative stress and lysozyme has, to the best of our knowledge, never been described previously. A zinc burst, described to occur inside macrophages (Botella et al, 2011), could indirectly affect the mechanisms of oxidative stress response, as it is known that zinc is able to compete with manganese (Kloosterman et al, 2008;McDevitt et al, 2011), a crucial metal in oxidative stress response, in protein binding. McDevitt et al (2011) found that extracellular zinc inhibits manganese acquisition in Streptococcus pneumoniae by competing for binding to the solute-binding protein PsaA.…”
Section: Resultsmentioning
confidence: 99%
“…A zinc burst, described to occur inside macrophages (Botella et al, 2011), could indirectly affect the mechanisms of oxidative stress response, as it is known that zinc is able to compete with manganese (Kloosterman et al, 2008;McDevitt et al, 2011), a crucial metal in oxidative stress response, in protein binding. McDevitt et al (2011) found that extracellular zinc inhibits manganese acquisition in Streptococcus pneumoniae by competing for binding to the solute-binding protein PsaA. Similarly, we have previously reported that the operon ef0575-ef0577, which encodes a PsaA-like solute-binding protein (EF0577), is upregulated by zinc and downregulated by manganese (Abrantes et al, 2011), revealing an E. faecalis manganese transporter that is modulated by zinc concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism(s) of copper toxicity in M. tuberculosis remain to be identified. The mechanism(s) of zinc ion toxicity may also include inactivation of iron -sulfur clusters (Xu and Imlay 2012) and inhibition of manganese uptake through transport competition in the bacterial perisplam (McDevitt et al 2011). In addition, it was shown recently that P-ATPase-mediated copper export is required for copper supply to periplasmic Cu,Zn-SOD and resistance to oxidative stress in Salmonella enterica (Osman et al 2013).…”
Section: Phagocyte Function Modulation By M Tuberculosismentioning
confidence: 99%